INTERNALISASI PENANAMAN NILAI-NILAI SPIRITUAL SISWA DI SMP 2 NEGERI BONDOWOSO - Yusuf, Lucky Damara; Firdausih, Firdausih; Ainurrofiq, Machbub (STAI Ihyaul Ulum Gresik, 2025)
Education is a basic need that shapes human mindset and personality. In this era of globalization, humans are not attacked through war, but through moral destruction. This is a consideration in educating and shaping children's personalities so that they do not fall into values that are not in accordance with Islamic teachings. Instilling spiritual values is the basis for providing a foundation for children in fighting world change. This study aims to describe: 1) Methods of Instilling Values, 2) Stages of Instilling Values, and 3) Results of Instilling Spiritual Values of Students at SMP 2 Negeri Bondowoso. This research is a qualitative descriptive research that aims to describe the methods, stages, and results of instilling spiritual values in students at SMP 2 Negeri Bondowoso. The subjects of the research were students, teachers, principals, and employees of SMP 2 Negeri Bondowoso. In collecting data using interview, observation, and documentation methods. The data used are the results of interviews with schools and students, field observations, and existing documentation.